Flexibility within the Heads of Muscle Myosin-2 Molecules - Billington, N; Revill, D J; Burgess, S A; Chantler, P D; Knight, P J (Journal of Molecular Biology, 2014)
We show that negative-stain electron microscopy and image processing of nucleotide-free (apo) striated muscle myosin-2 subfragment-1 (S1), possessing one light chain or both light chains, is capable of resolving significant amounts of structural detail. The overall appearance of the motor and the lever is similar in rabbit, scallop and chicken S1. Projection matching of class averages of the different S1 types to projection views of two different crystal structures of apo S1 shows that all types most commonly closely resemble the appearance of the scallop S1 structure rather than the methylated chicken S1 structure. Methylation of chicken S1 has no effect on the structure of the molecule at this resolution: it too resembles the scallop S1 crystal structure. The lever is found to vary in its angle of attachment to the motor domain, with a hinge point located in the so-called pliant region between the converter and the essential light chain. The chicken S1 crystal structure lies near one end of the range of flexion observed. The Gaussian spread of angles of flexion suggests that flexibility is driven thermally, from which a torsional spring constant of 23 pN·nm/rad2 is estimated on average for all S1 types, similar to myosin-5. This translates to apparent cantilever-type stiffness at the tip of the lever of 0.37 pN/nm. Because this stiffness is lower than recent estimates from myosin-2 heads attached to actin, we suggest that binding to actin leads to an allosteric stiffening of the motor–lever junction.
Keywords: ePrints migration